1878 Miss. Laws 175 - (:unkn) unknown (My University, 1878)
Ch.46 § 1: Prohibited the carrying of a concealed Bowie knife, pistol, brass knuckles, slungshot or other deadly weapon. Excepted travels other than "a tramp." Punishable by fine of $5-100.
Keywords: CARRY - CONCEALED